2010
DOI: 10.1108/02640471011081960
|View full text |Cite
|
Sign up to set email alerts
|

The impact of internet use on teaching, learning and research activities in Nigerian universities

Abstract: Purpose -The purpose of this paper is to assess the impact of internet resources and the evaluation of their usefulness on teaching, learning and research in Nigerian universities with particular emphasis on Obafemi Awolowo University (OAU), Ile-Ife, Osun State, Nigeria. Design/methodology/approach -The paper is based on a descriptive survey using questionnaires for data collection. The respondents constitute students (750) and academic staff (115) from OAU. Descriptive statistics (frequency counts and percent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 11 publications
2
13
1
Order By: Relevance
“…In the Nigerian context, the finding of the study affirms recent research findings by Ajala et al (2010), Nwezeh (2010, and Popoola (2008) but contradicts results of some studies that were conducted in the early 2000s (Ehikhamenor, 2003a(Ehikhamenor, , 2003bJimba & Atinmo, 2000). The current finding of the study, which aligns with global literature, is attributed to a relative increase in the level of awareness of the potential effect of electronic resources on research productivity in Nigeria (compared with the early 2000s when electronic resources were just being introduced in Nigerian universities).…”
Section: Testing Of Hypothesessupporting
confidence: 70%
“…In the Nigerian context, the finding of the study affirms recent research findings by Ajala et al (2010), Nwezeh (2010, and Popoola (2008) but contradicts results of some studies that were conducted in the early 2000s (Ehikhamenor, 2003a(Ehikhamenor, , 2003bJimba & Atinmo, 2000). The current finding of the study, which aligns with global literature, is attributed to a relative increase in the level of awareness of the potential effect of electronic resources on research productivity in Nigeria (compared with the early 2000s when electronic resources were just being introduced in Nigerian universities).…”
Section: Testing Of Hypothesessupporting
confidence: 70%
“…learning, grades and participation in class and co-curricular activities. ( Nwezeh, 2010)said that university education is unique because students are not only engaged in taking lectures regularly but they are also doing research work all the time. And for research internet is the best source of information as it contains the latest firsthand information and it also provides detailed knowledge about a topic from its historical background to its future horizons.…”
Section: International Journal Of Academic Research In Business and Smentioning
confidence: 99%
“…(Norzaidi & Salwani, 2009). Many researchers found that technology impacts positively on students' academic performance (Osunade, 2003;Norzaidi & Salwani, 2009;Nwezeh, 2010;Eastman et al, 2011). They found that by adopting technology, students not only participate well in classes but their grades also improve.…”
Section: International Journal Of Academic Research In Business and Smentioning
confidence: 99%
“…More people are now contributing to the generation of online applications, like movies, games, e-news, blogs, mobile phones, and e-learning (Shah et al, 2001). Academic staff frequently use the internet to receive general teaching materials, as a referral to additional lecture materials, and to improve their access to scholarly resources (Nwezeh, 2009). Teachers are more eager to perform web-reinforced teaching and are expected to use blogs and social network sites in their own class instruction (Kiyici, 2010).…”
Section: Online Learning Behavior Patternsmentioning
confidence: 99%
“…Changchien et al (2004) stated that due to the diversity in individual usage behaviors, cognitive needs and personality, further research into methods of clustering users may be quite interesting and helpful. Some studies suggested sorting online use patterns by users' age (Shah et al, 2001), while others explored the length of experience, access time, and frequency of online use patterns (Akporido, 2005;Donnermeyer and Hollifield, 2003;Nwezeh, 2009). Other than taking up the descriptive statistics, researchers also surveyed using user behavior factor analysis to investigate usage patterns among various users (Teo, 2001;Torkzadeh and Dhillon, 2002).…”
Section: Investigating User Behavior Patternsmentioning
confidence: 99%